KINERJA AGRIBISNIS KEDELAI DI KABUPATEN BANYUMAS - Wijayanti, Irene Kartika Eka; Putri, Dindy Darmawati; Kusnaman, Djeimy; Mulyani, Altri; Saputro, Wahyu Adhi (Fakultas Pertanian, Universitas Janabadra, 2024)
Banyumas Regency is one of the soybean producers in Central Java. The development of soybean agribusiness will be successful if the performance of all sub systems is well integrated. This research aims to examine the performance of the soybean agribusiness system in Banyumas Regency. The research location was determined purposively on the basis of four main soybean producing sub-districts in Banyumas Regency, including Kebasen, Jatilawang, Banyumas, and Kembaran. The research sample of 101 people was determined using a simple random sampling method from 1,867 soybean farmers. The data used is data from the 2022 planting season. The input supply, cultivation, harvest and post-harvest handling, marketing and support subsystems were analyzed using the average percentage index of perceptions of soybean farmers. Based on the agribusiness system approach consisting of upstream, farming, agro-industry, marketing and supporting subsystems, it shows that the performance of the soybean agribusiness subsystem in Banyumas district obtained an average performance score for the entire soybean agribusiness subsystem of 3.58 in the good category. The highest value is in the upstream sub system and the lowest is in the farming sub system. Thus, various policies are needed to improve the performance of soybean farming in order to realize the welfare of soybean farmers in Banyumas Regency. Keywords: performance; agribusiness system; soya bean INTISARIKabupaten Banyumas merupakan salah satu produsen kedelai di Jawa Tengah. Pengembangan agribisnis kedelai akan berhasil apabila kinerja semua sub system nya terintegrasi dengan baik. Penelitian ini bertujuan untuk mengkaji kinerja system agribisnis kedelai di Kabupaten Banyumas. Lokasi penelitian ditentukan secara purposive atas dasar empat kecamatan penghasil utama kedelai di Kabupaten Banyumas, diantaranya Kebasen, Jatilawang, Banyumas, dan Kembaran. Sampel penelitian sebanyak 101 orang ditentukan menggunakan metode simple random sampling dari 1.867 petani kedelai. Data yang digunakan adalah data musim tanam tahun 2022. Subsistem penyediaan input, budi daya, penanganan panen dan pascapanen, pemasaran dan penunjang dianalisis dengan menggunakan persentase indeks rata-rata persepsi petani kedelai. Berdasarkan pendekatan sistem agribisnis yang terdiri atas subsistem hulu, usahatani, agroindustri, pemasaran dan penunjang menunjukkan bahwa kinerja subsistem agribisnis kedelai di kabupaten Banyumas memperoleh skor kinerja rata untuk keseluruhan subsistem agribisnis kedelai sebesar 3,58 dengan kategori baik. Nilai tertinggi pada sub system hulu dan terendah pada sub sistem usahatani. Dengan demikian diperlukan berbagai kebijakan untuk meningkatkan kinerja usahatani kedelai guna mewujudkan kesejahteraan petani kedelai di Kabupaten Banyumas. Kata kunci: kinerja; system agribisnis; kedelai